A long-term, strategic approach to evidence generation and knowledge translation in NSW, Australia - Sarah Thackway; Danielle Campbell; Tina Loppacher (Sax Institute, 2017)
There is a growing body of literature about the barriers to, and enablers of, the use of research evidence in policy and practice. Research funders are in a unique position to influence activities aimed at promoting research use. During the past decade, NSW (New South Wales) Health has systematically built and invested in an integrated population and health services research portfolio made up of different types of investment and policy focuses. Each of these investments has an explicit focus on translation. Ensuring a long-term, sustained, strategic approach to priority-driven research generation, true coproduction of evidence and effective knowledge translation will continue to deliver results for NSW. The NSW Population Health Research Strategy 2017-2021, currently in development, will have a strong emphasis on fostering environments and actions that promote the use of research in policy and practice.